Why is Loose Part an important learning medium for early childhood development? - Budiarti, Erna; Darmayanti, Rani (Jurnal Caksana : Pendidikan Anak Usia Dini, 2020)
Early infants are good at imitation and are passionate learners who learn via play. They are curious and actively seek new information. To develop its qualities, early infancy needs appropriate play. Educational play materials and instruments are used in play. Loose sections media games help kids grow. This study reviews the literature on loose-part learning materials and suggests actions to improve early childhood development. A descriptive qualitative systematic literature review (SLR) using Miles and Huberman's analysis of 2010–2020 papers was used. The articles examined Google Scholar search results for "learning media" and "loose part," "loose part media" and "PAUD learning," and "loose part media" and "PAUD learning" with "cognitive abilities" in early childhood education. Harzing's publish or perish app aided the search. The publications are from respected national and international journals and were published in 2010–2020. The study focuses on Play Group (KB) and Kindergarten (TK) early childhood education at PAUD institutions. Find open-access papers with 25 references and detailed information, including PDF files. This study's findings concern the method. Classroom action research and analysis usually use descriptive qualitative research methods. Research typically involves 10–15 5- to 6-year-olds. Art and creativity are linked to cognitive development. Wood, bamboo, plastic, and recycled packaging are common loose-part materials. Loose party invitations have received little attention. Teachers' lack of experience managing loose component learning materials in PAUD causes most problems. Include invitation-based groups to boost children's multifarious development, use loose components more diversely to promote variation, and attend workshops to improve teachers' pedagogical skills.